Quantitative design of drug compatibility by weighted modification method. - Zheng Qing-shan; Sun Rui-yuan (Acta Pharmacologica Sinica, 2016)
AIM: To set up a new method for designing and quantitatively analyzing drug compatibility. METHODS: Drugs for compatibility were divided into 6 dose levels which were evenly distributed to 6 compound groups according to a fixed design. A new mathematical model was set up to fit the dose-effect data of 6 groups. The coefficients, obtained from the model, reflected the dose-effect relationship and the important degree of every drug in combination. According to the coefficients, the drugs in compatibility could be distinguished into principal drug, synergist, inferior, antagonist, and assistant. Because compatibility in the maximal effect group was nearly (or was) an optimal one in 6 groups, the doses in the group were taken as a base for further modification which considered interaction among drugs. The results of the modification were demonstrated by further experiment. This method was applied to design and to quantitatively analyze the compatibility of allantoin, metronidazole, and dexamethasone sodium phosphate by 2 effect indices in mice. RESULTS: This new method was able to effectively determine important degree of drugs in combination, and to optimize their doses for designing compatibility. CONCLUSION: This weighted modification method is a highly efficient, accurate, and practical means for designing and quantitatively analyzing drug compatibility.